2010
DOI: 10.1007/s12237-010-9264-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to Shellfish Harvest Area Closure Decision Making Using GIS, Remote Sensing, and Predictive Models

Abstract: Currently, many states use precipitation information to regulate periodic closures of shellfish harvest areas based on a presumptive relationship between rainfall and bacteria concentration. We evaluate this relationship in four South Carolina estuaries and suggest new predictive models that integrate remote sensing precipitation data with additional environmental and climatic data. Model comparisons using Akaike's information criterion, tenfold cross-validation, and model r 2 values show substantial and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Fecal bacteria models have been attempted in limited applications [46], for example in beach recreation areas [47], storm water ponds [48] and shellfish management settings [49]. These models use different predictors, including in-situ water temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal bacteria models have been attempted in limited applications [46], for example in beach recreation areas [47], storm water ponds [48] and shellfish management settings [49]. These models use different predictors, including in-situ water temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…First, remote sensing allows rainfall data to be collected and averaged over watersheds. According to Kelsey et al (2010), areally averaged rainfall values provide more predictive capability for bacteria concentrations than point estimates obtained from rain gauges. Second, remotely sensed data products can be collected, collated, and processed in automated fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Following rainfall events and subsequent high flow conditions, fluxes in E. coli were 50 times higher than under normal weather conditions [7]. Kelsey et al [8] developed a predictive model of bacterial contamination of shellfish using remote sensing precipitation data along with additional environmental and climatic data. The study findings indicated a substantial influence of temperature and salinity on bacteria concentrations.…”
Section: Introductionmentioning
confidence: 99%